2014
DOI: 10.1093/rpd/ncu081
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary results of indoor radon survey in V4 countries

Abstract: The measurements of radon activity concentration carried out in residential houses of V4 countries (Hungary, Poland and Slovakia) show that radon levels in these countries considerably exceed the world average. Therefore, the new radon data and statistical analysis are required from these four countries. Each partner chose a region in their own country, where radon concentration in residential buildings was expected to be higher. The results of the survey carried out in the period from March 2012 to May 2012 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…The high Discomfort index (DI) at low temperature and high RH increasing the radon concentrations attributed to the permeability of the soil that mobilizes radon into the spaces in the basement buildings. This was found in agreement with the observations of the previous investigators [2,3,6,9,22] and observed within the standard permissible limits [8,24,25,26]. The high radon concentrations in car parks from sites GVI and GIV attributed to the influence of (a) external sources from the soil, (b) poor car parks maintenance in these areas and, (c) exhaust smoke emanated from the cars due to frequent car parking by the residents in such populated areas.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The high Discomfort index (DI) at low temperature and high RH increasing the radon concentrations attributed to the permeability of the soil that mobilizes radon into the spaces in the basement buildings. This was found in agreement with the observations of the previous investigators [2,3,6,9,22] and observed within the standard permissible limits [8,24,25,26]. The high radon concentrations in car parks from sites GVI and GIV attributed to the influence of (a) external sources from the soil, (b) poor car parks maintenance in these areas and, (c) exhaust smoke emanated from the cars due to frequent car parking by the residents in such populated areas.…”
Section: Discussionsupporting
confidence: 94%
“…A 24h monitoring in the car park using Rad7 revealed the peak radon concentrations at 8 (Fig.3). Radon concentrations was moderately high during the months of November and February (early and late winter) and comparatively low in October and March (onset and late winter) (Fig.2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Radon (222Rn), which is considered a noble gas, is colorless, odorless, tasteless and naturally radioactive ( 2 ). When inhaled, a fraction of radon and its progeny are transported to the lungs ( 3 ) and produce severe biological damage, which could eventually lead to lung cancer ( 4 - 6 ); alpha decay of radon and its progeny causes this radiation damage. Even though soil is the main source of indoor radon ( 7 ), studies have shown a positive correlation between the radon exhalation rate and its concentration in building materials ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Integration measurements of indoor radon and thoron in houses were performed in the framework of the project "Harmonization of determining the radiation dose of the population originating from radon in V4 countries" (Műllerová et al, 2014). The objective of the project was to elaborate a common measurement protocol of the Visegrad countries for the measurement of indoor radon and thoron concentration (the placement of detectors, type of detectors, questionnaires).…”
Section: Introductionmentioning
confidence: 99%